Misinformation, Radicalization and Hate Through the Lens of Users - Ribeiro, Manoel Horta; Almeida, Virgílio A. F.; Meira Jr, Wagner (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2020: Anais do XXXIII Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2020.11373, 2020)
The popularization of Online Social Networks has changed the dynamics of content creation and consumption. In this setting, society has witnessed an amplification in phenomena such as misinformation and hate speech. This dissertation studies these issues through the lens of users. In three case studies in social networks, we: (i) provide insight on how the perception of what is misinformation is altered by political opinion; (ii) propose a methodology to study hate speech on a user-level, showing that the network structure of users can improve the detection of the phenomenon; (iii) characterize user radicalization in far-right channels on YouTube through time, showing a growing migration towards the consumption of extreme content in the platform.